2014
DOI: 10.2478/pjst-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Accuracy of Batak Lite Tests Used for Assessing Coordination Motor Abilities in Wrestlers

Abstract: Introduction. The aim of this work was to assess selected validity criteria of motor tasks included in Batak Lite. The tasks are used to control coordination motor abilities in athletes of different sports. Material and methods. Twenty male Greco-Roman wrestlers from the sports school SMS in Radom were included in the study. They were 17-18 years of age and their training experience was 4-7.5 years long. The validity of motor tasks was determined on the basis of two criteria, i.e. reliability and diagnostic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…A small number of researchers [ 17 , 44 46 ] examined response time closely related to wrestling performance. The views regarding the role of response time in a wrestling fight are ambiguous [ 17 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of researchers [ 17 , 44 46 ] examined response time closely related to wrestling performance. The views regarding the role of response time in a wrestling fight are ambiguous [ 17 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the time to respond is of crucial importance in wrestling and was identified in the cluster of success factors. Whitley, Montano [ 46 ], Gierczuk, Bujak [ 44 ], Gierczuk et al [ 17 ] share the view that wrestlers’ performance depends on response time. Although the role of response time in wrestling may seem obvious, there is still not enough information about it.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of judo and sports jujutsu, special fitness tests are often used, on the basis of acceptable throws in sports combat [ 23 ]. Intermediate performance tests (reaction speed and manual efficiency), such as the Batak Lite test [ 15 , 24 ] or the balance test, as an element of the motor coordination ability, have an indirect effect on the combat effectiveness [ 25 , 26 , 27 , 28 ]. The test involving gripping of Ditrich rod deserved its role in the sports that require fast reaction, such as in fencing [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors assumed that the specific motor skills and the ability to perform specific motor activities are determined by the structure and functions of the organism. These motor abilities can be identified and developed as part of the structure and functions of the living organisms [ 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Among the various motor skills, we can distinguish skills that are especially important for particular sports.…”
Section: Introductionmentioning
confidence: 99%
“…In another study showed that technology development can be used as an instrument to monitor physical activity, training, and provide measurements of a broad and detailed data set so as to provide data for a more objective evaluation of training strategies and new approaches on how to apply knowledge (Passfield & Hopker, 2017). There had been many studies on reaction that used training tool or technology-based tool, such as measuring instruments in research (Gierczuk & Bujak, 2014) which were devoted to training the reaction time of Batak Pro which has twelve LED lights. There had been previous studies on wrestling that had used this measuring instrument.…”
Section: Discussionmentioning
confidence: 99%